Penerapan Metode Preference Selection Index (PSI) Penentuan Penilaian Kinerja Fasilitator di BBPPMPV BBL Medan - Artika Suri Ayangda; Victor Maruli Pakpahan; Darjat Saripurna (Asosiasi Riset Teknik Elektro dan Informatika Indonesia, 2024)
Organizational performance includes various indicators such as productivity, work quality, efficiency, and innovation. Challenges often arise in the performance evaluation process when not supported by an adequate system. Additionally, facilitators play a crucial role in achieving goals, but poor selection of facilitators can lead to problems like lack of participation, poor time management, and inability to resolve conflicts, negatively impacting productivity and decision quality. This study aims to develop a support system that improves performance evaluation and facilitator roles at BBPPMPV-BBL Medan. The system is expected to simplify performance evaluation, enhance resource management effectiveness, and assist facilitators in carrying out their tasks optimally. The research findings indicate that this support system provides more accurate, structured, and effective performance evaluation, while enhancing facilitators' ability to maintain focus, manage time, and resolve conflicts. Implementing this system at BBPPMPV-BBL Medan contributes to increased productivity, efficiency, and performance quality, and enables proper recognition of high-performing individuals or teams.